Genomic dissection of pod shattering in common bean: mutations at non‐orthologous loci at the basis of convergent phenotypic evolution under domestication of leguminous species. (12th January 2019) - Rau, Domenico; Murgia, Maria L.; Rodriguez, Monica; Bitocchi, Elena; Bellucci, Elisa; Fois, Davide; Albani, Diego; Nanni, Laura; Gioia, Tania; Santo, Debora; Marcolungo, Luca; Delledonne, Massimo; et al.
Summary: The complete or partial loss of shattering ability occurred independently during the domestication of several crops. Therefore, the study of this trait can provide an understanding of the link between phenotypic and molecular convergent evolution. The genetic dissection of 'pod shattering' in Phaseolus vulgaris is achieved here using a population of introgression lines and next‐generation sequencing techniques. The 'occurrence' of the indehiscent phenotype (indehiscent versus dehiscent) depends on a major locus on chromosome 5. Furthermore, at least two additional genes are associated with the 'level' of shattering (number of shattering pods per plant: low versus high) and the 'mode' of shattering (non‐twisting versus twisting pods), with all of these loci contributing to the phenotype by epistatic interactions. Comparative mapping indicates that the major gene identified on common bean chromosome 5 corresponds to one of the four quantitative trait loci for pod shattering in Vigna unguiculata . None of the loci identified comprised genes that are homologs of the known shattering genes in Glycine max . Therefore, although convergent domestication can be determined by mutations at orthologous loci, this was only partially true for P. vulgaris and V. unguiculata, which are two phylogenetically closely related crop species, and this was not the case for the more distant P. vulgaris and G. max . Conversely, comparative mapping suggests that the convergent evolution of the indehiscent phenotype arose through mutations in different genes from the same underlying gene networks that are involved in secondary cell‐wall biosynthesis and lignin deposition patterning at the pod level. Significance Statement: Genetic mapping of the genetic architecture of pod shattering in common bean, and comparisons with other crops, have allowed the genetic basis of phenotypic convergent evolution to be defined. This definition indicates that different genes can be responsible for the shattering phenotype in legumes.